To the Conception of Existoencephalic System of Cooled Brain. Part 6. Fractal Geometry of Functional Architecture of Ultrastructural Elements of Central Thermoregulation Synaptic Apparatus Under Hypothermia and Hibernation - Marchenko, V. S.; Grischenko, V. I.; Babiychuk, V. G.; Babiychuk, G. A.; Marchenko, L. N. (Problems of Cryobiology and Cryomedicine, 2003)
State of hypothermia during cooling and hibernation is accompanied by fractal dynamics of functional architecture of synaptic apparatus of thermoregulation center. During cooling there are observed the specific changes in ultrastructural elements of synapses, which are characteristic for a long-term potentiation, a parasynaptic instrument, related to vegetative memory, is formed. Fractal dimension of ECG and EEG can serve as an integral index of an organism vegetative status.